2009
DOI: 10.1161/hypertensionaha.108.125252
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Impaired Potassium Handling With Dual Renin-Angiotensin-Aldosterone Blockade in Chronic Kidney Disease

Abstract: The combination of an aldosterone receptor antagonist added to an angiotensin-converting enzyme inhibitor has been demonstrated to reduce cardiovascular and renal end points in hypertensive humans but can produce hyperkalemia in the common clinical setting of impaired renal function. We investigated the effects of dual therapy on acute and chronic potassium handling in hypertensive humans with renal impairment by conducting a randomized crossover clinical trial of 4 weeks of 40 mg lisinopril/25 mg spironolacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Hyperkalemia stimulates aldosterone secretion, which also increases the fractional potassium excretion (27). Patients who have CKD and have been given a potassium load actually maintain their S K levels when compared with control subjects, strongly supporting the presence of compensatory extrarenal mechanisms of potassium loss (28). Patients with …”
Section: Discussionmentioning
confidence: 98%
“…Hyperkalemia stimulates aldosterone secretion, which also increases the fractional potassium excretion (27). Patients who have CKD and have been given a potassium load actually maintain their S K levels when compared with control subjects, strongly supporting the presence of compensatory extrarenal mechanisms of potassium loss (28). Patients with …”
Section: Discussionmentioning
confidence: 98%
“…Taken together, our current findings indicate that renal dysfunction greatly puts patients at risk for hyperkalemia irrespective of the dosage of TMP-SMX. In kidney diseases, an impaired production of aldosterone results in abdominal potassium excretion (25,26). Accordingly, the potassium-sparing effects of TMP-SMX are presumably accentuated in patients with kidney insufficiency even at low-dose TMP-SMX.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, as illustrated in Tables 2 and 3, there were no between-group differences in 24-hour urine sodium or potassium excretion and no between-group differences in fractional excretion of potassium or potassium excretion rate. Other investigators found that the effects of lisinopril and spironolactone therapy on renal potassium excretion do not fully account for the observed increase in serum potassium that this regimen induces in patients with CKD (23), but no studies have compared different regimens. Even while adjusting for urinary sodium, potassium, and creatinine clearance in our study, the significant differences in serum potassium change between losartan and placebo and between spironolactone and placebo persisted.…”
Section: Discussionmentioning
confidence: 99%